Joint association of air pollutants on cardiometabolic multimorbidity - Liang Xia; Shan Zhou; Liyuan Han; Weifeng Sun; Hongpeng Sun (Scientific Reports)
Abstract We estimated the association between combined exposure to air pollutants and the development of cardiometabolic multimorbidity (CM) and all-cause mortality. An air pollution score was calculated to determine the combined exposure to five air pollutants. CM was defined as the instance of at least two types of diseases. A genetic risk score (GRS) was calculated for each individual. A multistate regression model was used to investigate the effect of the combined associations of air pollutants on each stage of CM progression. After multivariable adjustment, the air pollution score was related with greater susceptibility of CM and all-cause mortality, and those with a high GRS for cardiovascular disease (CVD) or coronary heart disease (CHD) and a high air pollution score had a greater susceptibility of incident CM and all-cause mortality. The multistate model revealed that the greater air pollution score was connected with the susceptibility of progressing from disease-free baseline to having one cardiometabolic disease, and next to CM, and eventually to death. Combined exposure to five air pollutants were related with greater susceptibility of CM and all-cause mortality in a dose-dependent style and is related with the progression of CM and with all-cause mortality.